2016
DOI: 10.1111/jomf.12383
|View full text |Cite
|
Sign up to set email alerts
|

Grandparents' Education and Infant Health: Pathways Across Generations

Abstract: Using data from the Fragile Families and Child Wellbeing survey linked to respondents’ medical records (N=2,870), this study examines the association between grandparents’ education and birth outcomes and explores potential pathways underlying this relationship. Results show that having a grandfather with less than a high school education was associated with a 93 gram reduction in birthweight, a 59% increase in the odds of low birthweight, and a 136% increase in the odds of a neonatal health condition, compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
(87 reference statements)
0
5
0
Order By: Relevance
“…Somewhat relatedly, grandparental wealth is measured as the average of maternal and paternal grandparents' family wealth. The impact of grandparental wealth on child wellbeing may differ between paternal and maternal linkages [74]. Therefore, efforts should be devoted to exploring whether and how the protective role of wealth might vary between paternal and maternal grandparents.…”
Section: Discussionmentioning
confidence: 99%
“…Somewhat relatedly, grandparental wealth is measured as the average of maternal and paternal grandparents' family wealth. The impact of grandparental wealth on child wellbeing may differ between paternal and maternal linkages [74]. Therefore, efforts should be devoted to exploring whether and how the protective role of wealth might vary between paternal and maternal grandparents.…”
Section: Discussionmentioning
confidence: 99%
“…Current data suggest that some of the intergenerational social influences on birth weight include education, geographical location, and other sociodemographic characteristics. For example, grandparents' educational attainment and residential environment have been associated with grandchildren's birthweight 213,214 . In the Fragile Families and Child Wellbeing Study, having a grandfather with less than a high school education was associated with a 93-gram reduction in birth weight and a 59% increase in odds of low birthweight 214 .…”
Section: Rationale For Epigenetic Effectsmentioning
confidence: 99%
“…For example, grandparents' educational attainment and residential environment have been associated with grandchildren's birthweight 213,214 . In the Fragile Families and Child Wellbeing Study, having a grandfather with less than a high school education was associated with a 93-gram reduction in birth weight and a 59% increase in odds of low birthweight 214 . An examination of multiple social and biological factors within the Aberdeen Children of the 1950s study revealed that both distal and proximal grandparental and parental life-course biological and social factors predicted child size at birth.…”
Section: Rationale For Epigenetic Effectsmentioning
confidence: 99%
“…One set of studies examine similarities between mothers' and daughters' birth weight outcomes, and the social processes—such as maternal income—mediating this association (Conley and Bennett 2000, Conley and Bennett 2001, Currie and Moretti 2003, Currie and Moretti 2007). Other studies identify risk factors and pathways of risk contributing to poor perinatal health that date back multiple generations, such as intergenerational transmissions of low maternal education (Kane 2015, McFarland, McLanahan et al In press). …”
Section: Social Relationships As a Key Preconception Social Conditionmentioning
confidence: 99%
“…Indeed, understanding not only the mother's early life course experiences through a more comprehensive lens of place and social relationships, but also understanding the experiences of her parents, which may have critically shaped her early life experiences, could lend a more comprehensive understanding of the set of risk factors leading to poor perinatal health. As previously noted, prior studies have laid the groundwork for exploring these associations (Conley and Bennett 2000, Conley and Bennett 2001, Currie and Moretti 2003, Currie and Moretti 2007, Kane 2015, McFarland, McLanahan et al In press), but much more work is needed to parse out these socially and biologically complex pathways. Furthermore, such explorations could expand our understanding of infant health as a mechanism transmitting social, health, and economic, disadvantage from one generation to the next (Case, Lubotsky et al 2002, Case and Paxson 2006, Kane 2015, Kane 2016).…”
Section: Promising Directions For Future Researchmentioning
confidence: 99%